DESKRIPSI RANTAI PASOK MEBEL BERBAHAN BAKU KAYU KELAPA (STUDI KASUS DI BLPT GMIM KAATEN KOTA TOMOHON) - Edzzuko Shiomy Tariang; Agnes Estephina Loho; Juliana Ruth Mandei (AGRI-SOSIOEKONOMI, 2018)
This study aims to describe the supply chain of coconut wood-based furniture (Case Study at the Technical Education Training Center or Kaaten BLPT, Tomohon City). This research was conducted forthree months from September to November 2017. The data used are primary and secondary data. Primary data was obtained through direct observation in the field and direct interviews with one coconutfarmer and two employees of the Technical Education Training Center (BLPT), so that the total respondents were three people. Secondary data is obtained from the company documents. The results showed that Supply Chain Furniture made from coconut wood from the BLPT Kaaten consists of four Main Chains, namely: Suppliers; Producer; Expedition Services; and End Consumers; with details starting from (a) Supplier of coconut wood raw materials spread in several regions, including Lemoh,Tanawangko, Airmadidi, Kembes, Tenggari, Kaima, Bitung, Lolak and Belang, (b) BLPT Kaaten for purchasing, production, sales, and shipping, (c) Expedition Services to send products from the port of Bitung outside the Sulawesi region, Java Island and to be exported to the destination country, (d) End Consumers. Two of the three streams found in the process of implementing Supply Chain Management are well managed, namely the flow of goods / products and information flow. These two streams have caused coconut wood-based furniture production to continue to operate.*eprm*.